A new approach of robust speed-sensorless control of doubly fed induction motor fed by photovoltaic solar panel - Mekki Mounira; Cherifi Djamila (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In this work, we presented the modelling and simulation of the electrical operation of a photovoltaic (PV) system adapted by an MPPT control, the latter is applied to the robust observer for the control of the speed without sensor of a double fed induction motor (DFIM).Our machine is powered by the PV system, where the chosen control is the direct field oriented control with sliding mode speed regulator is used for the control of this machine which is powered by two pulse-width modulation (PWM) voltage inverters, finally the speed estimation of induction motor with observer based dual feed in sliding mode is presented. The simulation results show the efficiency of the proposed method.